Isolation of Entomopathogenic Lysinibacillus sphaericus from Sewage at Some Housing Complex in Mataram City and Evaluation of Its Toxicity Against Aedes aegypti Larvae in Laboratory - Dewi, Novia Devi Kusuma; Hidayati, Ernin; Sarkono, Sarkono; Prasedya, Eka Sunarwidhi; Suryadi, Bambang Fajar (Universitas Brawijaya, 2022)
The aims of this study were to isolate Lysinibacillus sphaericus from sewage at some housing complex in Mataram city and evaluate its toxicity against third Aedes aegypti larvae. The bacteria collected from mud taken from diluted sewage and objected to heat shock procedure at 80ÂºC for 30 minutes. The microbiological culture was done using a Nutrient Agar solid medium and incubated at 30ÂºC for 72 hours. Bacterial characterization was done based on bacterial colony morphology, cell morphology, cell physiology, and cell biochemistry characteristics. Toxicity test on 3rd Aedes aegypti larvae was done for 24, 48, and 72 hours applying Nutrient Broth medium with various dilution. From this study total of 11 isolates of Lysinibacillus sphaericus were isolated, only three isolates showed a high killing rate against Ae. aegypti in 24-hour observation. They were isolate Bs9-2-3 (LC50 24-hour value was 1.75 x 104 cell/mL), isolate Bs9-1-5 (LC50 24-hour value was 6.23 x 104 cell/mL) and isolate Bs2-1-2 (LC50 24-hour value was 7.17 x 106 cell/mL). These local isolates of L. sphaericus had good potential to be developed for bacterial-based biopesticide/biolarvicide for battling Aedes mosquito larvae in the near future.